BIOCHEMICAL CHANGES IN THE EXTRACELLULAR MATRIX OF RAT LIVER DURING CHRONIC ALCOHOL INTOXICATION - Mykytenko, A.O.; Akimov, O.Ye.; Yeroshenko, G.A.; Shevchenko, O.M.; Neporada, K.S. (World of Medicine and Biology, 2022)
Excessive alcohol consumption is a global health problem worldwide, resulting in more than 3 million deaths each year. The purpose of this work was to study the biochemical markers of intercellular matrix metabolism of rat liver under the conditions of chronic alcohol intoxication modeling. The experiments were performed on 30 male Wistar rats, weighing 180-220 g. The animals were divided into 2 groups: І – control; ІІ – chronic alcohol intoxication. Animals were removed from the experiment on days 10, 14, 21 and 28. We studied concentration of glycosaminoglycans, oxyproline and sialic acids in rat liver. We established that the greatest depolymerization of proteoglycans was on the 21st day, the highest intensity of collagenolysis was on the 14th day. Glycoproteins underwent the greatest catabolism on the 28th day. Chronic alcohol intoxication on the 28th day led to increased breakdown of glycoproteins and proteoglycans of the extracellular matrix of the liver, and increased the intensity of collagenolysis.
Keywords: alcohol; liver; glycosaminoglycans; sialic acids; oxyproline; extracellular matrix